(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
The present study was carried out to assess the levels of different heavy metals like chromium (Cr), lead (Pb), cadmium (Cd), iron (Fe), copper (Cu), zinc (Zn) and manganese (Mn) on red amaranth vegetable irrigated with polluted river water. Atomic Absorption Spectrometer was used for analyzing the heavy metals in the samples. The results indicated a substantial build-up of heavy metals accumulation in red amaranth irrigated with polluted river water. The ranges of various metals in red amaranth samples irrigated with polluted river water were 0.450.93, 0.1470.175, 42.33479.73, 1.3112.04, 3.7135.11 and 10.9142.9 ?g g-1 for Cr, Pb, Fe, Cu, Zn and Mn, respectively. Cadmium concentration was below the detection limit (0.01 ?g g-1) of the method used in the analysis. However, the regular monitoring of levels of these metals from effluents and sewage, in vegetables and in other food materials is essential to prevent excessive build-up of these metals in the food chain. In general, our results indicated that using polluted river water had no significant variation in growth and yield of red amaranth from the crops irrigated with fresh water. Res. Agric., Livest. Fish.3(1): 53-65, April 2016